Prediksi Penjualan Menggunakan Metode Fuzzy Mamdani Pada PT. XYZ - Yuni Roza; Yonky Pernando; Ihsan Verdian; Eka Lia Febrianti; Ilwan Syafrinal (JURIKOM (Jurnal Riset Komputer), 2022)
A corporation makes a choice based on sales forecasts for the next period based on residual inventory from the previous period as well as forecasts of the number of requests in the next period. A forecast is an estimate of future demand based on some predictive characteristic, which is frequently based on time series, historical data. And because these things are unknown, we need the correct way to overcome the uncertainty of future sales in order to avoid issues in sales. The length of the forecast decision-making process is affected by the problems encountered. The fuzzy mamdani approach, also known as the max-min method, is used in this sales prediction procedure to map issues from input to output. Based on the results of the calculations performed in this approach, it may create sales forecasts with the necessary data's accuracy and develop a useful system with an efficient system display that is simple to use.